Optimization of Stimulation of Children's Growth and Development Using Educational Game Tools in Widya Karya Kindergarten: Community Service - Putu Indah Sintya Dewi; Aditha Angga Pratama; Putu Wahyu Sri Juniantari Sandy; Ni Made Dwi Yunica Astriani (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
The growth and development of early childhood is an asset for future generations. The better the growth and development of children, the better the future generation of the nation will be. The purpose of this service is to optimize the stimulation of children's growth and development in kindergarten schools. The service method is divided into three stages, namely the planning, implementation, and evaluation stages. The target of this service is early childhood in kindergarten totaling 45 children. The activity lasts for a full month and the result is that optimal stimulation can increase children's growth and development where in particular development as measured using the Denver development screening test found that most children grow according to their age.